Racial and Gender Diversity Among Students and Faculty in EHAC-Accredited Environmental Health Sciences Programs: Trend Analysis from 2009 to 2021. - Balanay, Jo Anne G; Mitchell, Leslie D; Richards, Stephanie L (Environmental Health Insights, 2022)
Diversity in the environmental health sciences (EHS) workforce is crucial in providing culturally sensitive services to diverse communities. This may be influenced by academic faculty training a diverse student body in the field of environmental health. This study aimed to characterize the diversity of students and faculty in EHS programs accredited by the National Environmental Health Science and Protection Accreditation Council (EHAC). A retrospective analysis was conducted on secondary data obtained from annual surveys administered to program directors in EHAC-accredited academic programs that included both undergraduate and graduate EHS degrees. The database covered surveys on gender and race that were conducted by EHAC for 12 academic years spanning 2009-2010 to 2020-2021. Results show most students (undergraduate and graduate) were female (54.4% and 52.1%, respectively) and white (61.0% and 50.7%, respectively). Increasing trends were observed over the last 12 years (2009-2021) in female undergraduate (from 53.7% to 59.8%) and graduate (from 47.1% to 60.3%) students and in non-white undergraduate students (from 40.0% to 48.2%). Most faculty (teaching in undergraduate and graduate programs) were male (64.4% and 64.3%, respectively) and white (77.9% and 92.1%, respectively). Increasing trends were observed from 2009 to 2021 in female faculty teaching undergraduate (from 27.7% to 42.2%) and graduate (from 31.3% to 42.1%) students. Native American, Alaska Native, Native Hawaiian, and Pacific Islander are consistently the most underrepresented racial groups in both undergraduate and graduate students and faculty. This study provides baseline data on the diversity of students and faculty in EHAC-accredited programs, which is important in informing future research and efforts to increase such diversity. Gender and racial disparity in EHS students and faculty needs to be addressed to provide necessary support to women and non-White constituents by institutional change in culture through active recruitment and by stronger collaboration between professional organizations and minority groups.